Kepatuhan Ibu Hamil Trimester III Dalam Mengkonsumsi Tablet Fe Di Wilayah Kerja Puskesmas Sukatenang Tahun 2023 - Jannah, Miftahul; Musmundiroh, Musmundiroh (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Abstract Anemia is still a problem in pregnant women with a prevalence of 48.9%. Prevention of anemia in pregnant women is done by giving a minimum of 90 Blood Supplement Tablets (TTD) during pregnancy and starting as early as possible. The aim of this research is to determine the factors that influence third trimester pregnant women's compliance in consuming Fe tablets. This research is an analytical survey with a cross sectional approach. The population in this study were all third trimester pregnant women who underwent ultrasound examinations in the Sukatenang Community Health Center Work Area in January-May 2023 with a total sample of 55 people. Data collection instruments using primary data, data analysis using univariate and bivariate analysis with the chi square test. The results showed that the variables education (P = 0.000), knowledge (P = 0.001), employment (P = 0.006), parity (P = 0.003), age (P = 0.014), and family support (P = 0.002) had a relationship significant, with the compliance of third trimester pregnant women in consuming Fe tablets. There is a significant relationship between education, knowledge, employment, parity, age and family support with third trimester pregnant women's compliance in consuming Fe tablets. The variable with the greatest relationship is education with an Odds Ratio (OR) value of 28.800. Pregnant women are expected to take part in posyandu activities and counseling or health education during pregnancy classes to increase knowledge about how to consume Fe tablets and pregnant women should always consume TTD during pregnancy and accompanied by consumption of nutritionally balanced foods to help the absorption of iron and iron. the food source.